Problems of using Hydrochlorothiazide Diuretic in Adult Diabetic Patient in Diabetic Clinic of Adama Hospital Medical College,East Shoa Zone ,Oromia Regional State, Ethiopia (Global Journal of Medical Research, 2015)
Abstract not found
Keywords: hyperglycemia; high and low insulin response; hypokalemia